Obtaining new silicon phthalocyanines as sensitizers with high singlet oxygen efficiency using the combined effect of light and ultrasound - Celep, Kevser; Atmaca, Goknur Yasa; Erdogmus, Ali (ELSEVIER, 2024)
This study focused on the synthesis of innovative silicon phthalocyanines featuring halogen substituents and explored novel approaches to cancer therapy, focusing on photodynamic therapy (PDT), sonodynamic therapy (SDT), and sonophotodynamic therapy (SPDT), trying to achieve increased singlet oxygen generation. For this purpose, 2-Chloro-4-methylphenol and 2-Bromo-4-methylphenol silicon phthalocyanines were synthesized and their sonochemical, photochemical and sono-photochemical abilities were measured and compared. By employing various analytical methods, including spectroscopic techniques, the compounds' behavior and reactivity were thoroughly examined. With the recorded measurements resulting in significantly high quantum yields, this research sheds light on the potential utility of the achieved sensitizers in combatting cancer through novel therapeutic avenues.
Keywords: Silicon phthalocyanine; Sono-photodynamic therapy; Photosensitizer; Singlet oxygen; Sono-photochemical; SONODYNAMIC THERAPY; PHOTODYNAMIC THERAPY; ZINC PHTHALOCYANINE; CANCER; SUBSTITUENTS; DERIVATIVES; EFFICACY; Chemistry